Glucagon-like peptide 1 (GLP-1) and eating - Gutzwiller, Jean-Pierre; Degen, Lukas; Heuss, Ludwig; Beglinger, Christoph (Physiology & behavior, 2004)
New information regarding gastrointestinal mechanisms that participate in the control of food intake has extended our understanding of appetite control. Although each new signaling pathway discovered in the gut is a potential target for drug development in the treatment of obesity, the growing number of such signaling molecules indicates that a highly complex process controls food intake. The present summary focuses on the role of glucagon-like peptide 1 (GLP-1) in this regulatory process. The different biological effects of GLP-1 (glucose-lowering properties, inhibition of appetite and food intake) provide a powerful impetus for development of GLP-1-based new drugs.